Beatriz González : desplazamientos - Gonzalez, Beatriz, 1938- (Editorial UTadeo, 2019)
The present exhibition and the accompanying texts come from a research-creation project developed by Mariana Dicker, María Alejandra Fajardo, Elkin Rubiano and Javier Gil. This exploration aims to think about the relationships between artistic creation and memory based on Beatriz González's artistic production of the last 20 years. The works of Beatriz González "confirm the possibility that art has to participate in the generation of other narratives, to express the past in another way, to express what is unexpressed in the official history. "Displacements" not only refers to the displaced, or those who are forced to migrate, or the souls who wander waiting for a burial, it also alludes to a series of artistic operations embedded in her creative processes." (HKB Translations) --Page [7].